Penggunaan Sekuen Fat Saturation (FS) Dalam Pemeriksaan MRI Knee Joint Kasus Osteosarcoma Di Instalasi Radiologi Rumah Sakit Di Jakarta - Saybivo Chandra; Ni Putu Rita Jeniyanti (Journal of Educational Innovation and Public Health, 2024)
Use Of Fat Saturation (FS) Sequences In MRI Knee Joint Examination Of Osteosarcoma Cases At Installation Radiology Hospital In Jakarta. Magnetic Resonance Imaging (MRI) is one of the medical support modalities used by doctors to diagnose a disease. MRI is capable of producing high resolution images of soft tissue and is capable of displaying various cuts (sagittal, axial, coronal and oblique) using high-strength magnetic fields and nuclei resonances of hydrogen atoms. Fat saturation is used to detect or extract signals from adipose tissue. Three methods can be used to achieve leanness: lean saturation, investment mulihan, and leaning phase. Fat sat is an umbrella term that encompasses several techniques, each with its own unique advantages, disadvantages, and strengths. During the MR imaging process, proton lipids and hydrogen protons from the air have different behaviors, and fat suppression techniques.The knee joint is a hinge joint with changes and is formed by both femoral condyles that are jointed with the superior surface of the tibia condyles. The patella is located above the smooth pateller surface of the femur and above that the patella slides as the joint moves. Osteosarcoma is a relatively common middle to high grade malignant soft tissue tumor, often with an early course affecting young patients, and most often involving soft tissue.